Self-compassion and maternal involvement: an analysis of the relationship in parents of elementary students with special needs - Pradana Chairy Azhar; Azri Ranuwaldy Sugma; Kiki Pratama Rajagukguk; Aisya Nabila Suhaimy (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Parents of children with special needs often experience emotional and psychological challenges in parenting, making self-compassion an essential internal resource that may influence parental involvement. This study aims to examine the relationship between self-compassion and maternal involvement among parents of children with special needs enrolled in elementary school. A quantitative correlational design was used involving 165 parents in Langkat, selected through purposive sampling. Data were collected using the Self-Compassion Scale (SCS), the Nurturant Mothering Scale (NMS), and the Mother Involvement Scale (MIS), and analyzed using the Pearson Product–Moment correlation test. The findings reveal a significant positive relationship between self-compassion and affective maternal involvement (r = 0.159, p < 0.05) and behavioral maternal involvement (r = 0.179, p < 0.05). However, no significant relationship was found between self-compassion and desired maternal involvement (p > 0.05). Although significant, both correlations were weak. These findings indicate that self-compassion may support emotional warmth and behavioral involvement in parenting children with special needs. This study contributes to the literature by providing empirical evidence on the relationship between self-compassion and maternal involvement among parents of children with special needs in the Indonesian context, particularly in Langkat.